The Impact of Government Expenditure on Banten Economic Growth in 2010 – 2017 - Zaidan Najmuddin (Ministry of National Development Planning Republic of Indonesia/Bappenas, 2020)
Government expenditure is one of the factors driving the economic growth of a region. During 2010 to 2017, realization of Banten government expenditure continued to increase from 11 trillion to 36 trillion. However, Banten's economic growth from 2011 to 2017 tended to slow down from 7.03 percent to 5.71 percent. This study aims to determine how the impact of government expenditure on Banten economic growth and identify government expenditure in the form of capital spending that has a positive effect on Banten economic growth. Capital spending as a component of government expenditure directly related to the government's development program is expected to be able to encourage economic growth in Banten. The method used in this study is the impact analysis of Banten Input-Output (I-O) Table 2010 and panel data regression analysis in eight districts/cities during 2010 to 2017. The results of analysis with IO Table show that government expenditure has a positive impact on Banten’s economic growth. Then the panel data regression analysis results show that all types of capital spending have a positive effect, but only spending for road, irrigation, network (BJIJ); and building (BGB) which have proven to have significant effects on Banten's economic growth.